Dynamics and Determinants of Energy Intensity in the Service Sector: A Cross-Country Analysis, 1980–2005 - Peter Mulder; Henri L.F. de Groot; Birte Pfeiffer (Tinbergen Institute, 2013)
We present a detailed analysis of energy intensity developments across 23 service sectors in 18 OECD countries over the period 1980-2005. We find that the shift towards a service economy has contributed to lower overall energy intensity levels in the OECD, but this contribution would have been considerably larger if the service sector had realized the same degree of energy efficiency improvements as the manufacturing sector. In most OECD countries actual energy intensity levels in the service sector tend to decrease relatively slow, especially after 1995. If we control this trend for the impact of structural changes within the services sector – by means of a decomposition analysis – we find that in about one-third of the OECD countries, energy intensity levels in the service sector have increased over time. The impact of structural changes on aggregate energy i ntensity dynamics in the service sector has increased considerably after 1995, highlighting a relatively poor energy efficiency performance within a wide range of service sectors. We show that the introduction of Information and Communication Technology (ICT) plays a potentially important role here. Using spatial panel data regression analysis, we find a limited role for energy prices in explaining variation in energy productivity, casting doubt on the effectiveness of price instruments to enhance energy efficiency in the service sector. In contrast, climate conditions have a clear impact on energy productivity, especially the number of heating days.
Keywords: O13; O47; O5; Q43; 330; energy intensity; convergence; decomposition; sectoral analysis; service sector